Modulation of alveolar macrophage activity by eugenol attenuates cigarette-smoke-induced acute lung injury in mice - Oliveira, Maria Clara Barbosa de; Melo, Paolo Oliveira; Silva, Marcos Henrique Gonçalves da; Silva, Flávio Santos da; Silva, Felipe Andrade Carvalho da; Araujo, Bruno Vinicios Silva de; Oliveira, Moacir Franco de; Correia, Aristides Tadeu; Sakamoto, Sidnei Miyoshi; Valença, Samuel Santos; Lanzetti, Manuella; Schmidt, Martina; et al. (Switzerland, 2023)
This study investigates the role of eugenol (EUG) on CS-induced acute lung injury (ALI) and how this compound is able to modulate macrophage activity. C57BL/6 mice were exposed to 12 cigarettes/day/5days and treated 15 min/day/5days with EUG. Rat alveolar macrophages (RAMs) were exposed to CSE (5%) and treated with EUG. In vivo, EUG reduced morphological changes inflammatory cells, oxidative stress markers, while, in vitro, it induced balance in the oxidative stress and reduced the pro-inflammatory cytokine release while increasing the anti-inflammatory one. These results suggest that eugenol reduced CS-induced ALI and acted as a modulator of macrophage activity.
Keywords: CIENCIAS DA SAUDE::MEDICINA; Cigarette; Macrophages; Pulmonary inflammation; Oxidative stress; Eugenol